Water power: the domestic and geostrategic dimensions of Turkey's GAP Project. Issue 5 (3rd September 2017) - Ozkahraman, Cemal
Abstract: The Southeastern Anatolia Project (Güneydogu Anadolu Projesi, GAP), which was designed for the socio-economic development of south-east Turkey, has multiple political and strategic dimensions. While GAP was intended to narrow the socio-economic gap between the south-east and the rest of Turkey through development of the region, and to secure Turkey's future energy needs, the associated hydro-politics intertwine domestic and geopolitics in relation to water flow to downstream riparian states Syria and Iraq, securing Turkey a geostrategic position in the broader Middle Eastern context in terms of regional hydro-hegemony, while also impacting on relations with Kurds at home and in surrounding states.